2023
DOI: 10.5194/egusphere-2023-837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stratospheric aerosol size reduction after volcanic eruptions

Abstract: Abstract. The stratospheric aerosol layer plays an important role in the radiative balance of earth primarily through scattering of solar radiation. The magnitude of this effect depends critically on the size distribution of the aerosols. The aerosol layer is in large part fed by volcanic eruptions strong enough to inject gaseous sulfur species into the stratosphere. The evolution of the stratospheric aerosol size after volcanic eruptions is currently one of the biggest uncertainties in stratospheric aerosol s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…9, 10 show the best agreement is for 𝑠 =1.6. This is consistent with analysis of Wrana et al (2021Wrana et al ( , 2023 for SAGE III/ISS observations at altitudes above ~ 20 km where the particle distributions are unimodal. Both the OMPS-LP and balloon data particle radius are ~0.1 μm at all altitudes.…”
Section: Validation Of Omps-lp Retrievals With In Situ Balloon Measur...supporting
confidence: 88%
See 2 more Smart Citations
“…9, 10 show the best agreement is for 𝑠 =1.6. This is consistent with analysis of Wrana et al (2021Wrana et al ( , 2023 for SAGE III/ISS observations at altitudes above ~ 20 km where the particle distributions are unimodal. Both the OMPS-LP and balloon data particle radius are ~0.1 μm at all altitudes.…”
Section: Validation Of Omps-lp Retrievals With In Situ Balloon Measur...supporting
confidence: 88%
“…This assessment is also consistent with (2012). The exception appears to be the Hunga-Tonga eruption where SAGE measurements support a smaller distribution width of 1.2 (Wrana et al, 2023) which leads to larger particle sizes consistent with balloon observations (Baron et al, 2023). We also found that the uncertainty caused by the algorithm's assumed phase function is minimized when using typical aerosol CRs although the uncertainty can reach ±12-±32% for volcanic aerosol.…”
Section: Aerosol Changes After Hunga Tonga-hunga Ha'apai (Ht) Volcano...supporting
confidence: 59%
See 1 more Smart Citation
“…The homogeneity and the persistence of the properties across the plume and in time are clearly visible. Using the same method, Wrana et al (2023) found σ values for other stratospheric volcanic plumes produced by the eruptions of Ambae in 2018, Raikoke and Ulawun in 2019, and La Soufrière in 2021, which are all larger, approaching 1.8-2.0 together with smaller sizes (Wrana et al, 2023), reinforcing the exceptional aspect of the HTHH eruption.…”
Section: Resultsmentioning
confidence: 80%
“…This density is not very different from that of the background, here around 2 cm −3 at the altitudes of the plume and 3 cm −3 for Wrana et al (2021) at 20 km in June 2017. For comparison, Wrana et al (2023) found density of 20-30 cm −3 in stratospheric volcanic plumes generated by other recent eruptions with similar sulfur injection but much smaller particles.…”
Section: Resultsmentioning
confidence: 85%